2019
DOI: 10.1186/s12917-019-1815-y
|View full text |Cite
|
Sign up to set email alerts
|

A spatial assessment of Nipah virus transmission in Thailand pig farms using multi-criteria decision analysis

Abstract: Background Thailand’s Central Plain is identified as a contact zone between pigs and flying foxes, representing a potential zoonotic risk. Nipah virus (NiV) has been reported in flying foxes in Thailand, but it has never been found in pigs or humans. An assessment of the suitability of NiV transmission at the spatial and farm level would be useful for disease surveillance and prevention. Multi-criteria decision analysis (MCDA), a knowledge-driven model, was used to map contact zones between local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 45 publications
(55 reference statements)
0
19
0
Order By: Relevance
“…In Cambodia, P. lylei bats were found to often forage in residential areas and visit palm trees used in the region as a source of date palm sap; thus, opportunities abound for bats to interact with humans and livestock in this country ( 41 ). Bat colony migration toward urban sites is further enhanced by the presence of hunters in rural areas ( 42 ) and deforestation (causing consequent damage to roosting trees and food sources) ( 43 ). Contamination of palm sap, which is consumed raw by persons in the region, with bat urine, saliva, or feces was found to be a major route of NiV transmission to humans during annual outbreaks in Bangladesh ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Cambodia, P. lylei bats were found to often forage in residential areas and visit palm trees used in the region as a source of date palm sap; thus, opportunities abound for bats to interact with humans and livestock in this country ( 41 ). Bat colony migration toward urban sites is further enhanced by the presence of hunters in rural areas ( 42 ) and deforestation (causing consequent damage to roosting trees and food sources) ( 43 ). Contamination of palm sap, which is consumed raw by persons in the region, with bat urine, saliva, or feces was found to be a major route of NiV transmission to humans during annual outbreaks in Bangladesh ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…To expand the model to cover the whole country, a field study to identify the current locations of bat colonies nationwide should be undertaken, together with increased data collection on other factors needed in the spatial risk model construction. However, the present study initially carried out a risk analysis of one of the hotspots identified in a previous study [35] using a more sophisticated analytical technique. Our methods could be applied more widely once more data are available.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on 2093 subdistricts located in the central plain of Thailand, where bat colonies and pig farms are highly concentrated. The spatial risk of NiV emergence was assessed using the multi-criteria decision analysis (MCDA) method, and the results were published previously [35]. In this study, we sought to expand on those results.…”
Section: Index Subdistricts Identification For the Spread Of Nivmentioning
confidence: 99%
See 1 more Smart Citation
“…By combining spatial geographic data and its weighted, it is converted into a decision map [18]. It has a wide range of applications, mainly in environmental studies, land suitability assessment and epidemiological risk area assessment [19][20][21]. In health geography, this approach can re ect the complexity of spatial risk factors that affect the disease occurrence and consider multiple criteria for better understanding of disease characteristics [18].…”
Section: Introductionmentioning
confidence: 99%